XBRL as an Accounting Information System Innovation: A Study of Application to Australian Financial Reporting - Sri Fattah Dewandaru Mahasin; Ardhan Setiyawan; Renjiro Nathanael; Muhammad Hisham Nafis; Helena Smith (PT Global Digital Sains Tekno, 2026)
Purpose: This study examines the role of eXtensible Business Reporting Language (XBRL) within Accounting Information Systems (AIS) and evaluates its implementation in Australia’s digital reporting ecosystem. It aims to identify the determinants of XBRL adoption, assess its contribution to reporting quality, and analyze how regulatory and technological infrastructures enable national-scale digital reporting. Method: A descriptive qualitative approach was applied, drawing on an extensive literature review comprising five core academic sources, international regulatory documents, and Australia’s Standard Business Reporting (SBR) framework. The analysis focuses on AIS–XBRL integration, policy development, and cross-institutional reporting practices involving ASIC, ATO, and APRA. Findings: The study finds that XBRL enhances reporting accuracy, transparency, comparability, and processing efficiency through standardized taxonomies and automated validation mechanisms. Within AIS, XBRL supports a unified source of financial data, reducing discrepancies and improving decision-making. Australia’s SBR initiative shows strong effectiveness due to robust regulatory coordination and technological readiness. However, challenges remain, particularly limited adoption among smaller entities, insufficient technical competencies, and high initial implementation costs. Implication: The findings highlight the strategic importance of XBRL for digital reporting, regulatory oversight, and national data governance. They emphasize the need for capacity-building, policy reinforcement, and technical support to ensure inclusive adoption, especially for SMEs. Originality: This study integrates AIS theory, digital reporting policy, and national-level XBRL implementation, offering new insights into cross-institutional reporting ecosystems and future directions for digital disclosure, including potential extensions into sustainability reporting.